Uncovering the Macroeconomic Factors Driving Household Consumption in Indonesia: A Short-Term and Long-Term Analysis - Basuki, Agus Tri (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the influence of gross domestic product (GDP), imports, population size, exchange rate, and manufacturing added value on household consumption in Indonesia. The data used covers the period 1980 to 2023, with macroeconomic variables obtained from the World Development Indicators. The analysis model applied is the dynamic Error Correction Model (ECM). The results show that both in the long and short term, GDP, imports, exchange rates, and manufacturing value added significantly affect household consumption in Indonesia. Meanwhile, the size of the population does not have a significant influence on household consumption in the short term. Based on these findings, it is recommended to policymakers to strengthen the manufacturing sector and manage exchange rate policies to make them more stable, to encourage sustainable household consumption. In addition, increasing trade policies that support exports and imports can help increase people's purchasing power. Increased investment in the manufacturing sector is also expected to result in more inclusive economic growth and increase household consumption. This research makes a significant contribution to understanding the dynamics of macroeconomic factors that affect household consumption in developing countries such as Indonesia. These findings can serve as a reference for further research into the influence of economic sectors on social welfare. In addition, the results of this study provide valuable insights for policymakers in formulating more holistic and sustainable economic development strategies.